Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/2014je004620
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of fracture‐filling raised ridges in Yellowknife Bay, Gale Crater: Window into past aqueous activity and habitability on Mars

Abstract: The ChemCam instrument package on the Curiosity rover was used to characterize distinctive raised ridges in the Sheepbed mudstone, Yellowknife Bay formation, Gale Crater. The multilayered, fracture-filling ridges are more resistant to erosion than the Sheepbed mudstone rock in which they occur. The bulk average composition of the raised ridges is enriched in MgO by 1.2-1.7 times (average of 8.3-11.4 wt %; single-shot maximum of 17.0 wt %) over that of the mudstone. Al 2 O 3 is anticorrelated with MgO, while Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 66 publications
3
71
0
Order By: Relevance
“…After the deposition of the lake bed sediments (most of which are fine, medium, and coarse grained sandstones [ Grotzinger et al ., ]), the first diagenetic features observed to form are raised ridges, nodules, and minibowls (hollows). All models of nodule formation agree on their early diagenetic nature, and hypothesis of formation are gas bubbles [ Leveille et al ., ; Siebach et al ., ; Stack et al ., ]. We note that some of the reactions in our models, for example, the reaction of Ekwir with GPW at 50°C, would produce a water vapor dominated gas phase.…”
Section: Discussionmentioning
confidence: 99%
“…After the deposition of the lake bed sediments (most of which are fine, medium, and coarse grained sandstones [ Grotzinger et al ., ]), the first diagenetic features observed to form are raised ridges, nodules, and minibowls (hollows). All models of nodule formation agree on their early diagenetic nature, and hypothesis of formation are gas bubbles [ Leveille et al ., ; Siebach et al ., ; Stack et al ., ]. We note that some of the reactions in our models, for example, the reaction of Ekwir with GPW at 50°C, would produce a water vapor dominated gas phase.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of Ca-sulfate veins is not distributed uniformly through the entire Curiosity path but remains persistent: no other diagenetic feature has been reported so widespread along the traverse. 79 Moreover, the Ca-sulfate veins cross other diagenetic features (such as nodules at the YKB formation, and cluster-like features at Pahrump Hills). 27,80 This suggests the occurrence of a late, quite-widespread precipitation of sulfates from groundwater.…”
Section: Ca-sulfate Detectionmentioning
confidence: 99%
“…A number of ChemCam analyses were performed on this target, including both 30-and 150-shot depth profiles. Layers of both high and low magnesium were observed that showed trends with depth [11]. These trends were ascertained by direct examination of the spectra.…”
Section: B Results From Depth Study On Target "Mcgrath"mentioning
confidence: 97%
“…features have been interpreted as fracture-filling cements that record variability in the depositing fluid composition [11].…”
Section: B Results From Depth Study On Target "Mcgrath"mentioning
confidence: 99%